Differential clearance and host-pathogen interactions of YopE- and YopK- YopL- Yersinia pestis in BALB/c mice. - Straley, S C (1989)
This study characterized infections in BALB/c mice by the nonpigmented Yersinia pestis KIM and its derivatives lacking the low-Ca2+-response virulence plasmid pCD1 or failing to express selected yersinial outer membrane proteins (YOPs). The parent Y. pestis showed net growth in the spleen by 2 h and in the liver after 7 h; exponential growth in both the liver and spleen culminated in death of the mice starting on day 4, with total bacterial numbers of less than 10(8) in the blood, liver, and spleen together. The histopathology progressed from microabscesses to extensive coagulative necrosis unaccompanied by further immigration of inflammatory cells. This, together with the relatively low bacterial numbers, suggests a toxigenic mechanism. YopE- or YopK- YopL- yersiniae were cleared from the spleen but grew in the liver after an initial lag. Their growth was curbed after 1 to 2 days and entered a plateau that lasted 5 to 6 days; viable numbers then decline rapidly. This suggests that these Yop- mutations distinguish, at least kinetically, between host responses in liver and spleen. Both strains caused acute inflammation in liver that evolved into structured lesions surrounded by progressively mononuclear inflammation suggestive of a granulomatous response. Accordingly, YOP E and YOPs K and L are necessary in the early days of the infection for net growth in spleen and prolonged growth in the liver; their absence is reflected morphologically by the emergence of cell-mediated immunity in the liver. The YopE- and YopK- YopL- mutants bound only slightly increased amounts of C3, suggesting that YOPs E, K, and L are protective through mechanisms other than interfering with the binding of complement.